Application of the Pythagorean Theorem as a Quick Solution in Solving Relativistic Momentum Problems - Rahmat, Firdaus Nur; Khasanah, Umi Uswatun; Sa'diyah, Halimatus; Rahmadani, Novi Fitri; Supriadi, Bambang (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The Pythagorean theorem is a fundamental concept in mathematics that is often used to solve various geometric problems. In physics studies, especially in relativistic momentum analysis, the application of this theorem can be a fast and effective solution. This article explores the application of the Pythagorean theorem in the context of relativistic momentum, where the speed and energy of objects approach the speed of light. By exploiting the quadratic relationship between the components of the relativistic momentum and energy vectors, the Pythagorean theorem allows for simpler and more efficient calculations. This research identifies the relationship between the Pythagorean theorem equation and the relativistic momentum equation through several steps. The first step involves calculating the Pythagorean theorem equation. The second step is to calculate Einstein's special relativity equations. The final step is to analyze the relationship between the two equations. In this case, the relativistic and Pythagorean momentum equations have similarities and one of the formulas can be used.